Hodnocení výkonnosti společnosti s využitím Balanced Scorecard - Štollerová, Radka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práce se zabývá problematikou hodnocení výkonnosti vybrané společnosti s využitím metody Balanced Scorecard. První část práce obsahuje cíle, metodiku a teoretická východiska pro danou problematiku. Další část je věnována představení vybrané společnosti, strategické a finanční analýze. V závěrečné části na základě výstupů provedených analýz je zpracován návrh implementace modelu BSC za účelem zvýšení výkonnosti společnosti.

The diploma thesis deals with the issues of evaluating the performance of a selected company using the Balanced Scorecard method. The first part of the thesis contains the goals, methodology, and theoretical basis for the issues. The next part is devoted to the introduction of the selected company, strategic and financial analysis. In the final part, based on the outputs of the analyzes, a proposal for the implementation of the BSC model is prepared in order to increase the performance of the company.
The Performance Evaluation of the Company using Balanced Scorecard
Keywords: měření výkonnosti; strategie; Balanced Scorecard; perspektivy BSC; strategická analýza; finanční analýza; performance measurement; strategy; Balanced Scorecard; BSC perspectives; strategy analysis; financial analysis